REFLECTION OF COMPARISONS IN ENGLISH AND KARAKALPAK FOLKLORE GENRES (SCIENCE TIME JOURNAL, 2025)
Folklore is essentially the quirky and colorful tapestry of tales, traditions, and beliefs that make up the cultural fabric of any society. English comparisons as cultural values can be viewed through the prism of various aspects of life, such as traditions, customs, values and worldview. These comparisons help to understand how English culture interacts with other cultures and how values shape people’s behavior and customs. This article will delve into these aspects, providing a comparative analysis of examples from English and Karakalpak folklore texts through the lens of comparisons.